2009
DOI: 10.4304/jcm.4.1.20-25
|View full text |Cite
|
Sign up to set email alerts
|

On an Orthogonal Space-Time-Polarization Block Code

Abstract: <p class="MsoNormal" style="text-align: left; margin: 0cm 0cm 0pt; layout-grid-mode: char;" align="left"><span class="text"><span style="font-family: ";Arial";,";sans-serif";; font-size: 9pt;">Over the past several years, diversity methods such as space, time, and polarization diversity have been successfully implemented in wireless communications systems. Orthogonal space-time block codes efficiently combine space and time diversity, and they have been studied in detail. Polarization diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…Compared to the summary contribution in [13], in addition to the detailed analytical modeling steps, the main difference is the GCMA algorithm and the related simulations. Although quaternion-valued wireless communication employing multiple antennas has been studied before, such as the design of orthogonal space-time-polarization block code in [14], to our best knowledge, it is the first time to study the quaternion-valued equalization and interference suppression/beamforming problem in this context. Moreover, the dual-polarised antenna pair or an array of them has a similar structure to the well-studied vector sensors or sensor arrays [15,16,17,18], where they are used mainly for traditional array signal processing applications.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the summary contribution in [13], in addition to the detailed analytical modeling steps, the main difference is the GCMA algorithm and the related simulations. Although quaternion-valued wireless communication employing multiple antennas has been studied before, such as the design of orthogonal space-time-polarization block code in [14], to our best knowledge, it is the first time to study the quaternion-valued equalization and interference suppression/beamforming problem in this context. Moreover, the dual-polarised antenna pair or an array of them has a similar structure to the well-studied vector sensors or sensor arrays [15,16,17,18], where they are used mainly for traditional array signal processing applications.…”
Section: Introductionmentioning
confidence: 99%
“…As such, these quaternion orthogonal designs (QODs) over quaternion variables can be used as building blocks for orthogonal space-time-polarization block codes (OSTBCs) [5][6][7][8][9]. By taking advantage of the view of a quaternion variable as a combination of complex variables, we have shown that it is possible to use QODs to increase the complex rate in a QOD beyond what is possible with a COSTBC.…”
Section: Introductionmentioning
confidence: 99%
“…1. Hence, each transmission channel is described by the channel gain matrix H (m) ; m = 1, 2, …, N, where In [7], we have utilized the representation of a quaternion variable s = z 1 + z 2 j as s = [z 1 , z 2 ], so that a quaternion matrix Q can be converted into a complex matrix with twice as many columns [6,7,9]. However, we have referred to the complex representation of Q again as Q It was possible to use the context (e.g., the implied size or domain) to determine which representation of Q was being utilized but ultimately lead to a confusion and an abuse of the notation.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the output of a quaternion-valued beamformer is also quaternion-valued, only two components of the quaternion are used to recover the SOI, which leads to redundancy in both calculation and data storage. However, with the development of quaternion-valued communications [14][15][16], it is very likely that in the future we will have quaternion-valued signals as the SOI, where two traditional complex-valued signals with different polarisations arrive at the antenna array with the same DOA. In such a case, a full quaternion-valued array model is needed to compactly represent the four-component desired signal and also make sure the four components of the quaternion-valued output of the beamformer are fully utilised.…”
Section: Introductionmentioning
confidence: 99%